النظرية السوسيولوجية وإشكالية الخلفية المعرفية لدراسة مشكلات المجتمع العربي - مزيوة, بلقاسم; مباركية, جمال (جامعة الوادي - University of Eloued, 2022)
تمخّضت النظرية السوسيولوجية عن خصوصيّة المجتمع الذي نشأت فيه، وبالتالي فهي وليدة لبيئته وظروفه، ولا يمكن إخفاء إلزامية الارتباط الوثيق والتفاعل المفترض بين البحث السوسيولوجي والواقع الاجتماعي المستهدف للدراسة، على اعتباره يستند على خصوصية ثقافية وتاريخية، حتى تكون البيانات والمعطيات المتعلقة بالواقع الاجتماعي حقيقية، وليست شكلا من أشكال تأثير مناقشات وتدخلات الفكر، وفي هذا السياق جاءت فكرة هذه الورقة العلمية لمناقشة موضوع الممارسة النظرية السوسيولوجية والخلفية المعرفية لمشكلات المجتمع العربي، وذلك من خلال محاولة الإجابة على الأسئلة الآتية: 1. كيف يتم اختيار ومعالجة مواضيع البحوث المتعلقة بمشكلات المجتمعات العربية؟ 2. كيف يقارب الباحث العربي التراث النظري والبحثي السابق، من أجل الاستفادة منه في صياغة الإطار التصوري لبحث مشكلات المجتمعات العربية؟ 3. هل تحقق الممارسة النظرية في البحوث المتعلقة بمشكلات المجتمعات العربية، دورها في إنتاج بحوث علمية تعالج هذه المشكلات؟. Abstract: Sociological theory resulted in the privacy of the society in which it arose, and therefore it is the result of its environment and conditions, and the obligatory close connection and supposed interaction between sociological research and the targeted social reality of the study cannot be hidden, as it is based on a cultural and historical privacy, in order for the data and the informations related to the social reality to be real, and not a form of the impact of discussions and thought interventions, and in this context the idea of this scientific paper came to discuss the topic of sociological theoretical practice and the knowledge background for studying the problems of Arab society, by trying to answer the following questions: 1. How are research topics related to the problems of Arab societies selected and addressed? 2. How does the Arab researcher approach the previous theoretical and research heritage, in order to benefit from it in formulating the conceptual framework for examining the problems of Arab societies? 3. Does theoretical practice in research related to the problems of Arab societies achieve its role in producing scientific research that addresses these problems?
قراءة تحليلية
مقال
Keywords: النظرية السوسيولوجية، الخلفية المعرفية، مشكلات المجتمع العربي، الواقع الاجتماعي; sociological theory, knowledge background, problems of Arab society, social reality